Efficacy and safety of PD-1/PD-L1 and CTLA-4 immune checkpoint inhibitors in the treatment of diffuse pleural mesothelioma: a systematic review and meta-analysis - Sun, Peiyuan; Song, Dandan; Ma, Ning; Hou, Shufu; Liu, Lei; Gao, Jing; Tian, Yanyan (Frontiers in Immunology, 2025)
BackgroundWhile clinical trials confirm the therapeutic value of PD-1/PD-L1 and CTLA-4 inhibitors in diffuse pleural mesothelioma, their real-world safety and efficacy profiles remain incompletely defined. This meta-analysis synthesizes clinical evidence to comprehensively evaluate these outcomes, addressing an urgent need for robust real-world evidence.MethodsPubMed, Embase, the Cochrane Library were systematically searched for relevant studies. Outcomes including median progression-free survival (mPFS), median overall survival (mOS), 1-year overall survival (1-y OS), 1 year progression-free survival (1-year PFS),objective response rate (ORR), disease control rate (DCR), complete response(CR),partial response (PR), stable disease(SD), progressive disease(PD), treatment-related adverse events (TRAEs) and ≥grade 3 TRAEs were extracted for further analysis. The risk of bias was assessed by subgroup analysis.Results14 articles with 1345 patients were identified and subjected to meta-analysis. With regard to survival analysis, the pooled mOS and mPFS were 6.66 months (95%CI 4.85-9.16) and 2.92 months (95%CI 2.23-3.83), respectively. In terms of tumor response, the pooled ORR and DCR were 21% (95%CI 6%-41%) and 49% (95%CI 27%-71%), respectively. The pooled AEs rate and ≥ grade 3 AEs rate were 94% (95%CI 86%-99%) and 44% (95%CI 30%-58%).ConclusionPD-1/PD-L1 inhibitors combined with CTLA-4 inhibitors have shown effective clinical responses in the treatment of Diffuse Pleural Mesothelioma (DPM). Although the incidence of adverse reactions is high, they are generally tolerable.Systematic Review Registrationwww.inplasy.com, identifier INPLASY202520045.